Influence of the liquid helium meniscus on neutron reflectometry data - Kinane, C.J.; Kirichek, O.; Charlton, T.R.; McClintock, P.V.E. (Физика низких температур, 2016)
Neutron reflectometry offers a unique opportunity for the direct observation of nanostratification in ³He–⁴He mixtures in the ultra-low temperature limit. Unfortunately the results of recent experiments could not be wellmodelled on account of a seemingly anomalous variation of reflectivity with momentum transfer. We now hypothesize that this effect is attributable to an optical distortion caused by the liquid’s meniscus near the container wall. The validity of this idea is tested and confirmed through a subsidiary experiment on a D₂O sample, showing that the meniscus can significantly distort results if the beam size in the horizontal plane is comparable with, or bigger than, the diameter of the container. The meniscus problem can be eliminated if the beam size is substantially smaller than the diameter of the container, such that reflection takes place only from the flat region of the liquid surface thus excluding the meniscus tails. Practical measures for minimizing the meniscus distortion effect are discussed.